2017
DOI: 10.1186/s12974-017-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hydrogen sulphide attenuates NLRP3 inflammasome-mediated neuroinflammation by suppressing the P2X7 receptor after intracerebral haemorrhage in rats

Abstract: BackgroundEmerging studies have demonstrated the important physiological and pathophysiological roles of hydrogen sulphide (H2S) as a gasotransmitter for NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome-associated neuroinflammation in the central nervous system. However, the effects of H2S on neuroinflammation after intracerebral haemorrhage (ICH), especially on the NLRP3 inflammasome, remain unknown.MethodsWe employed a Sprague–Dawley rat of collagenase-induced ICH in the present study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 37 publications
6
72
0
Order By: Relevance
“…Studies have shown that oral administration of uridine can increases synaptic membranes and dendritic spines in rodents, signi cantly elevated striatal dopamine, tyrosine hydroxylase (TH) activity in 6-OHDA model [41]. S-adenosine methionine can reduce microglial aggregation and neuroin ammatory by increasing plasma hydrogen sulphide [42], which play neuroprotective role in central nervous system. Therefore, the decrease of Prevotella_copri will participate in the occurrence and progression of PD by leading loss of dopaminergic neurotransmission and neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oral administration of uridine can increases synaptic membranes and dendritic spines in rodents, signi cantly elevated striatal dopamine, tyrosine hydroxylase (TH) activity in 6-OHDA model [41]. S-adenosine methionine can reduce microglial aggregation and neuroin ammatory by increasing plasma hydrogen sulphide [42], which play neuroprotective role in central nervous system. Therefore, the decrease of Prevotella_copri will participate in the occurrence and progression of PD by leading loss of dopaminergic neurotransmission and neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing taurine can upregulate the content of H 2 S and reduce neutrophil infiltration and glial activation, downregulate the expression of inflammatory mediators and P2X7R, and reduce the inflammatory response, thereby improving the condition of WMI . Previous study also demonstrated that endogenous H 2 S reduces NLRP3‐mediated neuroinflammation by inhibiting the P2X7 receptor in rats with ICH . Another study showed that curcumin could inhibit neuroinflammation and alleviate WMI after ICH .…”
Section: Repair or Recovery Mechanism And Strategymentioning
confidence: 98%
“…28,29 Zhao et al found that ICH could significantly reduce the production of endogenous hydrogen sulfide (H 2 S) in the brain and that H 2 S weakened the inflammatory damage mediated by NOD-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) through the purinergic P2X7 receptor (P2X7R) signaling pathway. 30 Wang et al reported that microglia also closely interact with the endothelial cells. ICH induced damage to the endothelial cells, resulting in a large number of CXC chemokine ligand (CXCL).…”
Section: Pathophys I Ology Of Wmi Af Ter Ichmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous reports [27][28][29][30] and the results of MTT assay (Supplementary Figure S1), we selected glucose, SAMe, NaHS and resveratrol at a concentration of 85 mM, 0.2 mM, 250 μM and 10 μM to treat HT-22 cells, respectively, and divided them into the following ve groups: control group (25 mM glucose), high glucose (HG) group (85 mM glucose), HG + NaHS group (85 mM glucose + 250 μM NaHS), HG + SAMe group (85 mM glucose + 0.2 mM SAMe) and HG + resvertatrol (RES) group (85 mM glucose + 10 μM resveratrol).…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%